2017
DOI: 10.1186/s13052-017-0358-8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus infection: advances and challenges in diagnosis, prevention and treatment

Abstract: Cytomegalovirus (CMV) is the most frequent cause of congenital infection worldwide, with an estimated incidence in developing countries of 0.6–0.7% of all live births. The burden of disease related to congenital CMV in substantial, as it is the leading non-genetic cause of sensorineural hearing loss and an important cause of neurodevelopmental disabilities in children. Despite its clinical significance, congenital CMV infection often goes undetected because the majority of infected infants are asymptomatic at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
191
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(214 citation statements)
references
References 57 publications
2
191
0
21
Order By: Relevance
“…Since the incidence of congenital CMV infection parallels maternal seroprevalence, the estimated incidence in developing countries is even higher, between 1 and 5% of all live births [4]. The two known main sources of primary CMV infection during pregnancy are through sexual activity and contact with young children [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the incidence of congenital CMV infection parallels maternal seroprevalence, the estimated incidence in developing countries is even higher, between 1 and 5% of all live births [4]. The two known main sources of primary CMV infection during pregnancy are through sexual activity and contact with young children [5].…”
Section: Discussionmentioning
confidence: 99%
“…The presentation in this latter group is a continuum of disease expression whose more common findings are petechiae, jaundice, hepatomegaly, splenomegaly, microcephaly, and other neurologic signs. Laboratory and imaging findings include thrombocytopenia, transaminitis, and direct hyperbilirubinemia, chorioretinitis, and neuroimaging abnormalities indicative of central nervous system (CNS) involvement [4]. 70% of the congenital CMV infection cases are reported that they may have microcephaly, and that half of these cases may have periventricular calcifications in Brain CT [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Это одна из наиболее частых из диагностируемых внутриутробных инфекций: про-тективные антитела к вирусу ЦМВИ обнаруживаются у 80% населения старше 35 лет, что свидетельствует о перенесенной подавляющим большинством латентной (бессимптомной) форме этой инфекции [1]. По другим данным, удельный вес серопозитивных матерей (имею-щих протективные антитела) среди социально незащи-щенных слоев населения достигает 100% [2,3]. Тяжелые генерализованные формы ЦМВИ отмечаются только у иммунокомпрометированных пациентов (новорожден-ные при внутриутробном трансплацентарном зараже-нии, дети первых месяцев жизни, пациенты, получающие иммунодепрессанты).…”
Section: обоснованиеunclassified
“…Тяжелые генерализованные формы ЦМВИ отмечаются только у иммунокомпрометированных пациентов (новорожден-ные при внутриутробном трансплацентарном зараже-нии, дети первых месяцев жизни, пациенты, получающие иммунодепрессанты). Не исключается интранатальное инфицирование (наличие вируса в вагинальном секрете) [1,2]. При постнатальном инфицировании возможны контактный или алиментарный (в т.ч.…”
Section: обоснованиеunclassified